Personalized treatment of malignant tumors during pregnancy. Issue 26 (30th June 2022) - Ulrikh, E.; Kalinina, E.; Dikareva, E.; Komlichenko, E.; Li, O.; Zhamborova, O.; Rizhinashvili, I.; Dzharbaeva, A.; Govorov, I.; Artemenko, V.; Bezrukikh, V.; Salogub, G.; et al.
Abstract : The combination of pregnancy and cancer is a challenge for the patient and a problematic clinical dilemma for the doctor. In this retrospective observational cohort study, we have tried to analyze our experience in the management of such patients. This review includes 41 patients with malignant neoplasms detected during pregnancy who received treatment at the Almazov National Medical Research Centre from 2015-2021. The majority of patients received treatment during pregnancy (n=26, 63.4%): chemotherapy – 19 (46.3%) (in 2 cases in combination with surgery), surgical treatment – 7 (17, 1%) patients. In most cases, delivery was at term (n=28, 68.3%). All children born at term were mature and had no growth restriction, regardless of whether the mothers received treatment during pregnancy or not. When detecting cancer during pregnancy, an immediate follow-up examination is required to assess the extent of the tumor and current fetal state. If pregnancy prolongation is requested, the treatment should not be postponed, except for systemic chemotherapy in the first trimester of pregnancy, pelvic radiation at any term.